2021
DOI: 10.3389/fgene.2021.686939
|View full text |Cite
|
Sign up to set email alerts
|

Causal Relationship Between Parathyroid Hormone and the Risk of Osteoarthritis: A Mendelian Randomization Study

Abstract: BackgroundPrevious studies have demonstrated an inverse association between parathyroid hormone (PTH) and the risk of osteoarthritis (OA). However, it remains unknown whether such association reflects causality. We aimed to apply a Mendelian randomization (MR) approach to investigate the causal association between PTH and OA.Materials and MethodsWe performed a two-sample MR analysis using summary statistics from 13 cohorts (PTH, N = 29,155) and a recent genome-wide association study meta-analysis (OA, N = 455,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…25 Higher genetically predicted levels of parathyroid hormone have been associated in two studies with lower OA risk (OR 0.67, 95% CI 0.50-0.90; OR 0.71, 95% CI 0.61-0.82), with sensitivity analyses in one of these studies also indicating the association unlikely to be due to pleiotropy. 26,27 There is modest support for a causal association of sex hormone-binding globulin with OA risk at the hip, but not the knee (OR 1.09, 95% CI 1.01-1.17), although again, further sensitivity analyses were unable to rule out the possibility of the association being secondary to horizontal pleiotropy. 28 There was little support for a causal association of OA risk with genetically predicted levels of testosterone, dehydroepiandrosterone sulfate, or dihydrotestosterone.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…25 Higher genetically predicted levels of parathyroid hormone have been associated in two studies with lower OA risk (OR 0.67, 95% CI 0.50-0.90; OR 0.71, 95% CI 0.61-0.82), with sensitivity analyses in one of these studies also indicating the association unlikely to be due to pleiotropy. 26,27 There is modest support for a causal association of sex hormone-binding globulin with OA risk at the hip, but not the knee (OR 1.09, 95% CI 1.01-1.17), although again, further sensitivity analyses were unable to rule out the possibility of the association being secondary to horizontal pleiotropy. 28 There was little support for a causal association of OA risk with genetically predicted levels of testosterone, dehydroepiandrosterone sulfate, or dihydrotestosterone.…”
Section: Resultsmentioning
confidence: 93%
“…In contrast, genetically predicted levels of insulin‐like growth factor 1 (IGF‐1) were robustly associated with higher OA risk, with sensitivity analyses (OR 1.49, 95% CI 1.21–1.83), including adjustment for a BMI PRS suggesting that the IGF‐1 PRS association with OA was unlikely to be due to pleiotropy with BMI 25 . Higher genetically predicted levels of parathyroid hormone have been associated in two studies with lower OA risk (OR 0.67, 95% CI 0.50–0.90; OR 0.71, 95% CI 0.61–0.82), with sensitivity analyses in one of these studies also indicating the association unlikely to be due to pleiotropy 26,27 . There is modest support for a causal association of sex hormone–binding globulin with OA risk at the hip, but not the knee (OR 1.09, 95% CI 1.01–1.17), although again, further sensitivity analyses were unable to rule out the possibility of the association being secondary to horizontal pleiotropy 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Mendelian randomization is a method of using measured variations in genes of known function to examine the causal effect of a modifiable exposure. Two Mendelian randomization studies were identified in our review, and both found a causative relation between decreased circulating PTH level and increased risk of hip and knee OA [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Efforts were made to exclude the influence of outliers on the causal assessment of exposure and outcome. Analyzing the impact of individual SNPs on the causal assessment, a “leave-one-out” analysis was performed for detection [ 29 ]. Furthermore, the normal distribution of the MR analyses was examined, and the MR robust adjusted profile score (MR-RAPs) method was employed.…”
Section: Methodsmentioning
confidence: 99%